Prospective, double-blind randomized study of comparison of analgesic efficacy of parenteral paracetamol and diclofenac for postoperative pain relief - Shah, Ushma D. (J Anaesthesiol Clin Pharmacol, 2019)
BACKGROUND AND AIMS: Injectable paracetamol has analgesic and antipyretic activities, especially used in postoperative period. The aim of this study was to assess the analgesic efficacy and safety of IV paracetamol in comparison with IV diclofenac for postoperative pain relief. MATERIAL AND METHODS: Randomly selected 120 patients who underwent elective surgery under general anesthesia were divided into two groups: group A (paracetamol group): patients received IV paracetamol (15 mg/kg)/100 mL, 30 min before completion of surgery over the period of 15 min (rounded of to 1 g), the selected cases were in range of 60-70 kg body weight. Group B (diclofenac group): patients received IV diclofenac (1 mg/kg) diluted in 100 mL NS, 30 min before completion of surgery over the period of 15 min (rounded of to 75 mg). Pain relief and side effects were observed in postoperative period. Statistical analysis of continuous data was done by unpaired t-test and Chi-square test was applied for discrete data. RESULTS: Both IV paracetamol and IV diclofenac were effective for postoperative pain relief. No significant differences were found between them for any measures of analgesic activity. Only minor and common adverse events were reported, with no overall differences between groups. CONCLUSION: Both paracetamol and diclofenac drugs are safe to provide analgesia through IV route in postoperative period without any major significant side effects.